Photon transfer : DN [lambda] - Janesick, James R. (SPIE Press monograph ;, 2007)
Photon Transfer is designed for a wide audience--from the novice to the advanced user already familiar with the method. For first-time users, the book's primary purpose is to give sufficient guidelines to accurately generate, calibrate, and understand imaging data products through the photon transfer method. The book contains more than 230 figures that present experimental CCD and CMOS data products and modeling simulations connected to photon transfer. Contents also provide hundreds of relations that support photon transfer theory, simulations, and data.